2020
DOI: 10.1007/s12015-020-10049-y
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-Derived Stromal/Stem Cells from Large Animal Models: from Basic to Applied Science

Abstract: Adipose-derived stem cells (ASCs) isolated from domestic animals fulfill the qualitative criteria of mesenchymal stem cells, including the capacity to differentiate along multiple lineage pathways and to self-renew, as well as immunomodulatory capacities. Recent findings on human diseases derived from studying large animal models, have provided evidence that administration of autologous or allogenic ASCs can improve the process of healing. In a narrow group of large animals used in bioresearch studies, pigs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 152 publications
0
17
0
Order By: Relevance
“…Several studies have demonstrated the plasticity of human and animal ASCs [62][63][64]. Consistently, there is extensive literature regarding the safety and efficacy of ASC-based therapies for the treatment of numerous diseases and injuries created in animal models of human diseases, including cardiovascular disease and musculoskeletal and cutaneous injuries [65]. The therapeutic potential of ASCs or Stromal Vascular Fraction cells (SVFs) has been confirmed not only in experimental animal models but also in an increasing number of human clinical trials [66][67][68].…”
Section: Stem Cell Types For Fibrotic Disorders Therapymentioning
confidence: 87%
“…Several studies have demonstrated the plasticity of human and animal ASCs [62][63][64]. Consistently, there is extensive literature regarding the safety and efficacy of ASC-based therapies for the treatment of numerous diseases and injuries created in animal models of human diseases, including cardiovascular disease and musculoskeletal and cutaneous injuries [65]. The therapeutic potential of ASCs or Stromal Vascular Fraction cells (SVFs) has been confirmed not only in experimental animal models but also in an increasing number of human clinical trials [66][67][68].…”
Section: Stem Cell Types For Fibrotic Disorders Therapymentioning
confidence: 87%
“…In this study, ACMs different in morphology and physical structure have been evaluated in vitro and after subcutaneous implant in mice. Firstly, ACMs were incubated with ASCs to assess the interaction between the acellular scaffold and mesenchymal stem cells, representing one of the cellular elements involved in regeneration and repair pathways [27]. According to the literature, the stimulation and differentiation of ASCs increase wound repair and regeneration ability by intensifying collagen secretion and deposition [9,14].…”
Section: Discussionmentioning
confidence: 99%
“…The cellular components of AdSVF can be resuspended in platelet-rich plasma (PRP), phosphate-buffered saline (PBS), or 0.9% sodium chloride (saline) to produce a ready-to-use solution (Bukowska et al. 2021 ). In addition, AdSVF can be expanded in vitro to obtain AdSVF-derived mesenchymal stem cells that differentiate into diverse lineages of cells (Han et al.…”
Section: Preparation Of Adipose-derived Stromal Vascular Fractionmentioning
confidence: 99%
“…Reproduced from Bukowska et al. ( 2021 ) under Creative Commons Attribution 4.0 International License ( https://creativecommons.org/licenses/by/4.0/ ).…”
Section: Therapeutic Potential Of Stromal Vascular Fractionmentioning
confidence: 99%